Western and Islamic Effectiveness of Ontology, Epistemology and Axiology of Science - Elly Damayanti Pulungan; Salminawati Salminawati; Sulastri Sulastri; Neysa Vania Nasution (Universitas Muhammadiyah Enrekang, 2023)
Abstract In studying the philosophy of science, of course, there are three objects of study that are always found as the main pillars of every philosophical study that should not be missed, namely known as ontology, epistemology and axiology. These three objects of study are interconnected with each other, but in understanding these three objects in the scientific shutter, there are differences in Western and Islamic effectiveness in interpreting them. This difference in perspective often makes Muslims mistaken and even blind to the understanding that the science in Islamic effectiveness is very special. For this reason, it is necessary to examine more deeply the differences between these two perspectives, which later hopefully readers, especially Muslims, will no longer be blind to the beauty of the Islamic perspective on Science. Starting from what is studied, how and what the science was created for. By using the library research method or literature review, the author obtains the results of the research that. There are very deep differences between the two perspectives of both Western and Islamic perspectives. Keywords : West and Islam, Ontology, Epistemology, Axiology of Science. PERSFEKTIF BARAT DAN ISLAM TERHADAP ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI SAINS Abstrak Dalam mengkaji filsafat ilmu tentunya ada tiga objek kajian yang selalu ditemui sebagai pilar utama setiap kajian filsafat yang tidak boleh terlewatkan, yaitu dikenal dengan istilah ontologi, epistemologi dan aksiologi. Ketiga objek kajian ini saling berhubungan satu sama lain, namun dalam memahami ketiga objek ini dalam rana keilmuan, terdapat berbedaan persfektif Barat dan Islam dalam memaknainya. Perbedaan cara pandang ini sering kali membuat umat Islam keliru dan bahkan buta pemahaman bahwasanya ilmu dalam persfektif Islam sangat istimewa. Untuk itu maka perlulah dirasa untuk mengkaji lebih dalam mengenai perbedaan kedua cara pandang ini, yang nantinya diharapkan pembaca khususnya umat Islam tidak lagi buta akan indahnya cara pandang Islam terhadap Ilmu. Mulai dari apa yang dikaji, bagaimana caranya dan untuk apa ilmu itu diciptakan. Dengan menggunakan metode penelitian library research atau kajian pustaka, Penulis memperoleh hasil penelitian bahwa. Terdapat perbedaan yang sangat dalam mengenai kedua cara pandang baik dari persfektif Barat maupun Islam. Kata Kunci : Barat dan Islam, Ontologi, Epistemologi, Aksiologi Sains.